Validation of the Organizational-Based General Self-Esteem Scale - Filosa, Lorenzo; Alessandri, Guido (Frontiers in Psychology, 2022)
Using data from four different samples of full-time employees (Ntotal = 2,474), the present study was aimed to introduce and demonstrate the validity and reliability of the Organizational-Based General Self-esteem Scale (OB-GSE) a new six-item self-report scale to measure organizational-based self-esteem (OBSE) at work. Results provided evidence of (1) validity (internal, external, and convergent), (2) reliability, and (3) temporal stability of the OB-GSE scale. All in all, results attested the usefulness and the effectiveness of the OB-GSE scale.